Trading Places: Microlevel Predictors of Women Who Commit Intimate Partner Homicide. Issue 4 (November 2019) - Szalewski, Alec; Huff-Corzine, Lin; Reckdenwald, Amy
Intimate partner homicide (IPH) research has established the importance of the offender's gender regarding motivations, situations, and structures present in the offense. However, little is known about female IPH perpetrators' microlevel characteristics, despite research indicating female IPH offense numbers are closer to males' than in other homicide types. To fill this gap, the current exploratory study assesses the likelihood of female-perpetrated IPH by the couples demographics, weapon type, relationship status, and regional location of the homicide. Using data from the Supplementary Homicide Reports (SHR), results show microlevel gender-specific differences. Female, compared to male, IPH perpetrators more often kill in intraracial, compared to interracial relationships, and are more likely to kill in dating rather than marital relationships.